Consensus statement on concussion in sport—the 5th international conference on concussion in sport held in Berlin, october 2016 - McCrory, P.; Meeuwisse, W.; Dvorák, J.; Aubry, M.; Bailes, J.; Broglio, S.; Cantu, R. C.; Cassidy, D.; Echemendia, R. J.; Castellani, R. J.; Davis, G. A; Ellenbogen, R.; et al. (British Journal of Sports Medicine, 2017)
The 2017 Concussion in Sport Group (CISG) consensus statement is designed to build on the principles outlined in the previous statements1-4 and to develop further conceptual understanding of sport-related concussion (SRC) using an expert consensus-based approach. This document is developed for physicians and healthcare providers who are involved in athlete care, whether at a recreational, elite or professional level. While agreement exists on the principal messages conveyed by this document, the authors acknowledge that the science of SRC is evolving and therefore individual management and return-to-play decisions remain in the realm of clinical judgement. This consensus document reflects the current state of knowledge and will need to be modified as new knowledge develops. It provides an overview of issues that may be of importance to healthcare providers involved in the management of SRC. This paper should be read in conjunction with the systematic reviews and methodology paper that accompany it. First and foremost, this document is intended to guide clinical practice; however, the authors feel that it can also help form the agenda for future research relevant to SRC by identifying knowledge gaps.